1993
DOI: 10.1002/hep.1840170315
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary cholesterol on bile formation and hepatic processing of chylomicron remnant cholesterol in the rat

Abstract: We have studied the coupling between hepatic uptake of chylomicron remnant cholesteryl ester and biliary excretion of cholesterol and bile acids in rats, after feeding them a cholesterol-free (control) or a high-cholesterol diet (1% wt/wt) for 2 wk. We equipped rats with permanent catheters in the bile duct, duodenum and heart to allow experiments in unanesthetized, unrestrained animals. Cholesterol feeding induced a 20% increase in plasma cholesterol concentration, a threefold increase in hepatic bile acid sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

1995
1995
2009
2009

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…This is probably because of the high basal level of bile acid synthesis on this diet, which was 3-fold increased compared with diet containing no cholesterol. 56 However, inhibition of hepatic ACAT may still contribute to the maintenance of this high basal level under conditions of a reduced transport of cholesterol to the liver by inhibition of intestinal ACAT. In addition, we found that there was no increase in the biliary excretion of cholesterol, indicating that ACAT inhibition does not result in a more lithogenic bile.…”
Section: Discussionmentioning
confidence: 99%
“…This is probably because of the high basal level of bile acid synthesis on this diet, which was 3-fold increased compared with diet containing no cholesterol. 56 However, inhibition of hepatic ACAT may still contribute to the maintenance of this high basal level under conditions of a reduced transport of cholesterol to the liver by inhibition of intestinal ACAT. In addition, we found that there was no increase in the biliary excretion of cholesterol, indicating that ACAT inhibition does not result in a more lithogenic bile.…”
Section: Discussionmentioning
confidence: 99%
“…'~' ,~~~ This finding is the more remarkable given the relatively minor contribution of plasma-derived to biliary lipid secretion. The application of liposomes to target-specific (phospho-)lipids to hepatocytes may phospho~ipids173.174 and cholestero167,1"7.1.58, 160,168,[175][176][177][178][179][180] be of valuable help to further dissect these proIn summary, the precise intracellular origins of the lipids, which are secreted into the bile, have not yet been identified indisputably. However, various novel experimental models offer promising opportunities t o approach these obscurities in the next few particularly when data were obtained to suggest that crystallization of cholesterol occurs from supersaturated vesicles.81~1ti3~210~214~217~21g~…”
Section: Obscurities In the Process Of Biliarymentioning
confidence: 99%
“…The application of liposomes to target-specific (phospho-)lipids to hepatocytes may phospho~ipids173.174 and cholestero167,1"7.1. 58,160,168,[175][176][177][178][179][180] be of valuable help to further dissect these pro-In summary, the precise intracellular origins of the lipids, which are secreted into the bile, have not yet been identified indisputably. However, various novel experimental models offer promising opportunities t o approach these obscurities in the next few…”
Section: Obscurities In the Process Of Biliary Lipid Secretionmentioning
confidence: 99%
“…Biliary cholesterol is mostly derived from circulating lipoproteins, which originate from the hepatic uptake of plasma high-density lipoprotein (HDL) and chylomicron remnants. [3][4][5][6][7][8] Thus, the potential interrelationship between lipoprotein metabolism-related genes and cholesterol gallstones requires further investigation. In particular, it has been found that polymorphisms in the apolipoprotein (APO)-B gene are associated with cholesterol gallstones in humans.…”
mentioning
confidence: 99%
“…In particular, the pathway for metabolism of dietary cholesterol involves the hepatic uptake of chylomicron remnants and the use of chylomicron cholesterol for biliary secretion. [5][6][7][8] Therefore, it is crucial to compare the effect of APO-B48 -containing lipoproteins with that of APO-B100 -containing lipoproteins on regulating both the hepatic availability of dietary cholesterol for bile secretion and the risk for diet-induced cholesterol gallstones. In the present study, we investigated intestinal cholesterol absorption, gene expression levels of intestinal and hepatic lipid transporters, hepatic cholesterol and bile salt biosyntheses, biliary lipid secretion, and cholesterol gallstone formation in lithogenic diet-fed "APO-B48 only" and "APO-B100 only" mice compared with identically treated control wild-type mice.…”
mentioning
confidence: 99%